2018
DOI: 10.1007/s00432-018-2653-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrantly expressed F-box proteins in squamous-cell lung carcinoma

Abstract: Our results provide evidence that FBXO45 and FBXO5 may play a key role in tumorigenesis and prognosis of SqCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…A recent study based on data collected from the TCGA and Gene Expression Omnibus (GEO) databases showed that the expression of FBXO45 and FBXO5 was apparently increased in squamous cell lung cancer (SqCLC) compared with normal lung tissues [122]. Similarly, a prognostic analysis conducted by the K-M plotter database also revealed that overexpression of FBXO45 and FBXO5 contributed to shorter overall survival in patients with SqCLC [122]. Further molecular experiments showed that knockdown of FBXO5 increased cell apoptosis but that knockdown of FBXO45 promoted EMT in SqCLC cells [122].…”
Section: Regulation Of Emt By F-box Proteinsmentioning
confidence: 99%
“…A recent study based on data collected from the TCGA and Gene Expression Omnibus (GEO) databases showed that the expression of FBXO45 and FBXO5 was apparently increased in squamous cell lung cancer (SqCLC) compared with normal lung tissues [122]. Similarly, a prognostic analysis conducted by the K-M plotter database also revealed that overexpression of FBXO45 and FBXO5 contributed to shorter overall survival in patients with SqCLC [122]. Further molecular experiments showed that knockdown of FBXO5 increased cell apoptosis but that knockdown of FBXO45 promoted EMT in SqCLC cells [122].…”
Section: Regulation Of Emt By F-box Proteinsmentioning
confidence: 99%
“…1). Compared with that in normal lung tissue, FBXO45 is highly expressed in squamous-cell lung carcinoma (SCLC) tissues according to TCGA and Gene Expression Omnibus data 21 . Compared with that in adjacent tissues, an increased level of FBXO45 was confirmed in SCLC tissues by reverse transcription polymerase chain reaction analysis.…”
Section: Fbxo45 Is Highly Overexpressed In Human Cancer Tissuesmentioning
confidence: 99%
“…Compared with that in adjacent tissues, an increased level of FBXO45 was confirmed in SCLC tissues by reverse transcription polymerase chain reaction analysis. Furthermore, it was also illustrated that high expression of FBXO45 was correlated with poor survival in patients with SCLC by obtaining data from the Kaplan-Meier plotter website and the TCGA database 21 . Consistent with the results in SCLC, FBXO45 expression was higher in gastric cancer tissues than in normal gastric tissues 22 .…”
Section: Fbxo45 Is Highly Overexpressed In Human Cancer Tissuesmentioning
confidence: 99%
See 2 more Smart Citations